On the stability of the extracellular hemoglobin of Glossoscolex paulistus, in two iron oxidation states, in the presence of urea - Carvalho, Francisco Adriano O.; Santiago, Patricia S. [UNESP]; Tabak, Marcel (Elsevier B.V., 2012)
The stability of the Glossoscolex paulistus hemoglobin (HbGp), in two iron oxidation states (and three forms), as monitored by optical absorption, fluorescence emission and circular dichroism (CD) spectroscopies, in the presence of the chaotropic agent urea, is studied. HbGp oligomeric dissociation, denaturation and iron oxidation are observed. CD data show that the cyanomet-HbGp is more stable than the oxy-form. Oxy- and cyanomet-HbGp show good fits on the basis of a two state model with critical urea concentrations at 220-222 nm of 5.1 +/- 0.2 and 6.1 +/- 0.1 mol/L, respectively. The three-state model was able to reveal a subtle second transition at lower urea concentration (1.0-2.0 mol/L) associated to partial oligomeric dissociation. The intermediate state for oxy- and cyanomet-HbGp is very similar to the native state. For met-HbGp, a different equilibrium, in the presence of urea, is observed. A sharp transition at 1.95 +/- 0.05 mol/L of denaturant is observed, associated to oligomeric dissociation and hemichrome formation. In this case, analysis by a three-state model reveals the great similarity between the intermediate and the unfolded states. Analysis of spectroscopic data, by two-state and three-state models, reveals consistency of obtained thermodynamic parameters for HbGp urea denaturation. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Urea; Optical absorption; Fluorescence emission; Circular dichroism; Glossoscolex paulistus; Three-state model and oligomeric stability